Normalization Without Resolution? Regional Peace Initiatives - Budiargo, Nadya Fitri; Paksi, Arie Kusuma (The Sunan Ampel Review of Political and Social Sciences, 2025)
This study analyzes the dynamics of "normalization without resolution" as manifested in the 2020 Abraham Accords to assess the extent to which regional peace initiatives can serve as instruments of stability in the Middle East or instead deepen internal fragmentation in Palestine. Using a qualitative method based on analytical case studies and John Galtung's conflict resolution theoretical framework, this study examines the shift from the 2002 Arab Peace Initiative consensus, which emphasized the principle of land for peace, to a realpolitik paradigm driven by security calculations in the face of Iran, economic interests, and US support. The results show that the Abraham Accords have only produced a transactional cold peace at the state level, creating a negative peace in the form of the absence of direct inter-state violence, but failing to achieve a positive peace based on structural justice. This normalization has effectively marginalized the Palestinian issue, weakened its bargaining position in international diplomacy, and exacerbated the political divide between Fatah and Hamas. Furthermore, the neglect of core issues such as refugee rights shows that this initiative reproduces historical inequalities. In conclusion, normalization without resolution reflects the paradox of hybrid peace: fragile elitist stability that ignores the need for substantive reconciliation. The implications of this study confirm that sustainable peace can only be achieved through inclusive transformation that places Palestinian national unity and structural justice as key prerequisites.